Pleural Effusions - Miki Arimura, Amanda; Rubira, Claudio José; Felisberto Junior, Gilmar [UNESP]; Abreu, Phillipe; Novellino, Pietro; Kepler Alvim Fiorelli, Rossano; Machuca, Tiago (Springer Nature, 2025)
All healthy humans have a small amount of pleural fluid responsible for the lubrication that facilitates normal lung respiration movements. This delicate balance of fluid is maintained by the oncotic, hydrostatic pressure, and lymphatic drainage; any disturbances in one of these systems can lead to a build-up of excess fluid between the layers of the pleura outside the lungs, which is known as pleural effusion.